Persistent Alterations in Plasma Lipid Profiles Before Introduction of Gluten in the Diet Associated With Progression to Celiac Disease. Issue 5 (22nd May 2019) - Sen, Partho; Carlsson, Cecilia; Virtanen, Suvi M.; Simell, Satu; Hyöty, Heikki; Ilonen, Jorma; Toppari, Jorma; Veijola, Riitta; Hyötyläinen, Tuulia; Knip, Mikael; Orešič, Matej
Abstract : OBJECTIVES: Celiac disease (CD) is a chronic enteropathy characterized by an autoimmune reaction in the small intestine of genetically susceptible individuals. The underlying causes of autoimmune reaction and its effect on host metabolism remain largely unknown. Herein, we apply lipidomics to elucidate the early events preceding clinical CD in a cohort of Finnish children, followed up in the Type 1 Diabetes Prediction and Prevention study. METHODS: Mass spectrometry–based lipidomics profiling was applied to a longitudinal/prospective series of 233 plasma samples obtained from CD progressors (n = 23) and healthy controls (n = 23), matched for human leukocyte antigen (HLA) risk, sex, and age. The children were followed from birth until diagnosis of clinical CD and subsequent introduction of a gluten-free diet. RESULTS: Twenty-three children progressed to CD at a mean age of 4.8 years. They showed increased amounts of triacylglycerols (TGs) of low carbon number and double bond count and a decreased level of phosphatidylcholines by age 3 months as compared to controls. These differences were exacerbated with age but were not observed at birth (cord blood). No significant differences were observed in the essential TGs. DISCUSSION: Our preliminary findings suggest that abnormal lipid metabolism associates with the development of clinical CD and occurs already before the first introduction of gluten to the diet. Moreover, our data suggest that the specific TGs found elevated in CD progressors may be due to a host response to compromised intake of essential lipids in the small intestine, requiring de novo lipogenesis.